Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Budy P. Resosudarmo (Faculty of Economic & Business Universitas Gadjah Mada, 2011)
NO. Penulis ---- Judul Artikel ---- Halaman 1. Budy P. Resosudarmo, Arief A. Yusuf, Djoni Hartono dan Ditya A. Nurdianto ---- Regional Economic Modelling for Indonesia : Implementation of IRSA-Indonesias ---- 287-309 2. Rahman Dano Mustafa ---- The Identification of Structural Break at Time Series Data on Indonesian Economy 1990Q1-2008Q4 : The Application of Zivot and Andrews’ Experiment ---- 310-324 3. Bramantyo Djohanputro ---- Market Return, Volatility, and Trading Volume Dynamics After Economic Crisis ---- 325-340 4. Mokhamad Arwani dan Suprehatin ---- The Influence of Satisfaction and Relationship Marketing on Loyalty with Individual Characteristics as a Moderator : A Case Study on Islamic Banking Customers in East Java ---- 341-358 5. Sri Haryati ---- Insolvent Foreign Private Bank : A Study on Merger and Liquidated Banks ---- 359-370 6. Linda Rambu Kuba Yowi ---- The Correlation Among the Factors of Implementation, the System Development, and the Result of Performance Measurement System : A Study Conducted in The Regency of Sumba Timur ---- 371-388 7. Leo Indra Wardhana dan Eduardus Tandelilin ---- Ownership and Agency Conflict Controlling Mechanism ---- 389-406 8. Willy Abdillah ---- Antecedent and Consequence of Social Computing Behavior for Social Network Sites : Perspective of Social Influence Theory ---- 407-442